The importance of belief dispersion in the response of gold futures to macroeconomic announcements - Smales, Lee; Yang, Y. (Elsevier BV, 2015)
We investigate the behaviour of gold futures around the release of macroeconomic announcements. Market activity, in terms of traded volume, returns, and volatility, responds to new information quickly, with the majority of the reaction complete within 90-s. Surprises on the announcement of unemployment rate and GDP have the largest impact. Contrary to prior results for the equity market, gold futures exhibit greater reactions to ‘good’ economic news (which is negative for gold prices) and the magnitude of the response does not appear to increase during recession. Importantly, we employ a novel measure of belief dispersion, and we are able to demonstrate that the market response to macroeconomic news is significantly larger when belief dispersion is wider.